Multi-component composite coated titanium dioxide and preparation method thereof

Through the multi -composite envelope technology, the composite oxide film layer is formed, which solves the problem of poor weather resistance in outdoor applications in titanium pinks, and realizes the effect of significantly improve the weathering performance and gloss of titanium pink, and meets the needs of high -performance coatings.

CN119371840APending Publication Date: 2025-01-28SHANGHAI TITANOS IND
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411460059.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing titanium dioxide products have poor weather resistance in outdoor applications and cannot meet the needs of high-performance coatings.

Method used

Using multiple composite envelope technology, through the composite superposition of the three envelope materials of silicon, cricket, and aluminum, a dense silicon oxide film layer, a dense oxide film layer, and the combined aluminum oxide film layer combined with dense and loose Improve the weather resistance of titanium pink.

Benefits of technology

It significantly improves the weather resistance and gloss of titanium pink powder, and meets the development needs of coatings in high weathering and emerging environmental protection fields such as ships, bridges, solar energy, and wind power.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005091612850000111
    Figure BDA0005091612850000111
  • Figure BDA0005091612850000121
    Figure BDA0005091612850000121
Patent Text Reader

Abstract

The invention relates to the field of chemical engineering, and particularly discloses multi-component composite coated titanium dioxide and a preparation method thereof. The preparation method of the titanium dioxide comprises the following steps: S1, mixing titanium dioxide slurry with a silicate solution, and then controlling the pH value by using an inorganic acid solution twice; s2, adding a zirconate solution within a certain period of time, and controlling the pH value by using an alkali solution; s3, adding a meta-aluminate solution within a certain period of time, and meanwhile, adding an inorganic acid solution in a countercurrent manner to control the pH value; s4, continuously adding a meta-aluminate solution within a certain period of time, and simultaneously adding an aluminum sulfate solution in a downstream manner to control the pH value; and S5, adjusting the pH value at the end point, continuously stirring and curing, and then homogenizing, filtering, washing, dehydrating, drying, crushing and carrying out organic treatment. The titanium dioxide prepared by the invention is relatively good in optical performance index and weather resistance, and can meet the development requirements of coatings in the fields of ships, bridges, solar energy, wind power and the like which are high in weather resistance and emerging in environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of chemical industry, specifically, to the technical field of titanium dioxide, and more specifically, to a multi-component composite coated titanium dioxide and a preparation method thereof. Background Art

[0002] Titanium dioxide is the best white pigment and an important chemical raw material. It is widely used in coatings, plastics, papermaking, inks and other fields due to its excellent chemical properties, stable chemical properties, high refractive index and good hiding power. However, titanium dioxide, especially rutile titanium dioxide, is a photoactive semiconductor material. 4+ Easily reduced to Ti 3+ It also releases highly oxidizing active oxygen species, which degrade the organic components in contact with it, causing related products such as paint coatings to change color, powder and lose gloss, that is, the weather resistance deteriorates, seriously affecting the performance and service life of the coating. In order to solve this problem, people usually post-treat the primary titanium dioxide, that is, primary titanium dioxide, during the industrial production process of titanium dioxide, and coat its surface with a layer of inert inorganic oxide film to reduce the photocatalytic activity of titanium dioxide itself, thereby improving the weather resistance of titanium dioxide.

[0003] However, due to the technical limitations of the coating process, the existing outdoor weather-resistant titanium dioxide is mostly a general-purpose titanium dioxide product with a binary composite coating and a medium-to-low coating amount. This general-purpose titanium dioxide product cannot meet the high weather resistance and other performance index requirements required by high-performance coatings, resulting in poor performance indicators of the final coating in outdoor applications. Summary of the invention

[0004] In order to solve the above technical problems, the present application provides a multi-component composite coated titanium dioxide and a preparation method thereof.

[0005] In the first aspect, the present application provides a method for preparing a multi-component composite coated titanium dioxide, which adopts the following technical scheme: A method for preparing a multi-component composite coated titanium dioxide comprises the following steps: S1. The titanium dioxide slurry and the silicate solution are stirred and dispersed to obtain a mixed slurry, wherein the temperature of the titanium dioxide slurry is 65-75°C, the mass concentration is 22-25%, the pH value is 9.0-11.0, and the amount of the silicate solution added is 3.5-3.8% of the mass of TiO2 in terms of SiO2, and then the temperature of the mixed slurry is controlled to 74-78°C, and the pH value of the mixed slurry is first adjusted and controlled to 8.8-9.0 with an inorganic acid solution within 180-200 minutes while stirring, and the first layer of dense silicon film deposition is completed, and then the inorganic acid solution is used to adjust and control the pH value of the mixed slurry to 7.5-7.8 within 90-100 minutes, and the second layer of dense silicon film deposition is completed, and then stirred and matured for 100-110 minutes; S2. The temperature of the mixed slurry is controlled to be 58-62°C, and the zirconate solution is continuously added within 200-220min while stirring, and the pH value of the mixed slurry is controlled to be 9.3-9.5 with an alkaline solution to complete the deposition of a dense zirconium film, wherein the amount of the zirconate solution added is 0.6-0.7% of the mass of TiO2 in terms of ZrO2, and then stirred and aged for 60min; S3. Continue to adjust and control the temperature of the mixed slurry to 60-67 ° C, and continuously add aluminate solution within 90-110 min while stirring, wherein the amount of the aluminate solution added is 2.0-2.5% of the mass of TiO2 in terms of Al2O3, and the pH value of the mixed slurry is controlled to 8.9-9.5 with an inorganic acid solution, and the inorganic acid solution is added in a countercurrent manner, and then stirred and matured for 50 min; S4. Continue to adjust and control the temperature of the mixed slurry to 48-55 ° C, and continuously add aluminate solution within 45-60 minutes while stirring, wherein the amount of the aluminate solution added is 1.2-1.5% of the mass of TiO2 in terms of Al2O3, and the pH value of the mixed slurry is controlled to 7.2-7.8 with aluminum sulfate solution, and the aluminum sulfate solution is added in a downstream manner, and then stirred and matured for 50 minutes; S5. The end point pH value of the mixed slurry is adjusted to 7.0-7.2, and the stirring and aging are continued for 90-100 minutes, and then the mixed slurry is homogenized, filtered, washed, dehydrated, dried, crushed and organically treated to obtain a multi-component composite coated titanium dioxide.

[0006] By adopting the above-mentioned technical scheme, the present application optimizes various parameters of the coating process according to the slurry state, pH control rate, temperature and stirring and dispersing conditions of different coating processes, realizes the composite superposition of multi-component silicon film, zirconium film and aluminum film, and forms a dense silicon oxide film layer, a dense zirconium oxide film layer, and a dense and loose aluminum oxide film layer on the surface of the primary titanium dioxide. On the basis of maintaining the excellent optical performance indicators of the primary titanium dioxide, the weather resistance of titanium dioxide is greatly improved, meeting the development needs of coatings in high weather resistance and emerging environmental protection fields such as ships, bridges, solar energy and wind power.

[0007] Among them, the silicon film deposited by adjusting different pH value ranges twice has a high degree of density, which can greatly increase the weather resistance of titanium dioxide, and coating the surface with a dense zirconium oxide film can further improve the gloss and light resistance of titanium dioxide, and further enhance the weather resistance of titanium dioxide. Continuing to coat two layers of aluminum oxide film in different forms can further improve the gloss of titanium dioxide and the stability of system dispersion, promote the stability of the overall weather resistance index of titanium dioxide, and facilitate the filtration and washing of subsequent products. According to the common knowledge and prior art in this field, technicians in this field can routinely exchange the order of coating silicon film and zirconium film in the application, that is, first coat a layer of dense zirconium film, then coat two layers of dense silicon film, and finally coat two layers of aluminum film. This application adopts the above three coating materials and designs an optimized combination of film layers, which can effectively block the lattice defects of titanium dioxide and realize the shielding effect of multi-layer material superposition, which not only improves its optical performance indicators, but also makes the final titanium dioxide product have high weather resistance and anti-powdering performance.

[0008] Specifically, before coating, the present application adjusts the agitator speed to 60-70r / min, uses alkali solution to disperse the titanium dioxide slurry well in the pH range of 9.0-11.0, and adds desalted water to reduce the mass concentration of the titanium dioxide slurry to 22-25%, which is beneficial to reduce the coating rate. After stirring and dispersing for 30-40 minutes, the titanium dioxide slurry is heated to 65-75°C.

[0009] Furthermore, the present application adjusts the agitator speed to 65-70r / min, adjusts the pH value of the titanium dioxide slurry to 10.5-11.0, heats the titanium dioxide slurry to 68-72°C to fully disperse the titanium dioxide particles, and controls the titanium dioxide mass concentration to 22-23%. A lower concentration is beneficial to improving the density of the subsequent coated silicon film.

[0010] In the step of coating the silicon film of the present application, the silicate solution adopts a sodium silicate solution, and its concentration is 150-180g / L in terms of SiO2. Further, the concentration of the sodium silicate solution is 170g / L in terms of SiO2. The present application adds the sodium silicate solution to the titanium dioxide slurry at one time and disperses it fully for 30-40min, so as to facilitate the subsequent coating of the dense silicon oxide film. Further, the present application adds the sodium silicate solution to the titanium dioxide slurry in an amount of 3.6% of the mass of TiO2 in terms of SiO2.

[0011] Since a higher temperature is more conducive to forming a dense film layer, but considering the comprehensive energy consumption and coating effect, the present application further controls the temperature of the mixed slurry to 74°C, and deposits a dense silicon film by adjusting the pH value in two stages with an inorganic acid solution at a speed of 50-55r / min. The inorganic acid solution uses hydrochloric acid with a mass concentration of 9-11%. Furthermore, the present application adjusts the speed to 55r / min.

[0012] In the step of coating the zirconium film of the present application, the zirconate solution adopts a zirconium sulfate solution, and its concentration is 165-175g / L in terms of ZrO2. The present application slowly and evenly adds the zirconate solution to the mixed slurry at a rotation speed of 60-65r / min within a certain period of time. A longer deposition time is more conducive to the formation of a dense zirconium film. Furthermore, the present application adjusts the rotation speed to 65r / min, controls the temperature of the mixed slurry at 60°C, sets the deposition time to 210min, and the amount of zirconate solution added in terms of ZrO2 accounts for 0.62% of the mass of TiO2.

[0013] In the step of the coated aluminum film of the present application, due to the deposition of zirconium oxide film first and then aluminum oxide film, the phenomenon of false thick slurry will occur when aluminum oxide film is deposited, resulting in particle agglomeration, so the application adjusts the agitator speed to 55-65r / min, preferably 60-65r / min, strengthens stirring ability, and enhances the dispersibility of particles. Under the above-mentioned stirring conditions, the application slowly and evenly adds aluminate solution to the mixed slurry within a certain period of time, and the aluminate solution adopts sodium aluminate solution, and its concentration is calculated as 145-170g / L with Al2O3, and further, the sodium aluminate solution calculated as 150-170g / L with Al2O3 is selected as concentration. In this step, the inorganic acid solution is sulfuric acid solution, and its mass concentration is 10%. The application adds sulfuric acid solution to the mixed slurry in a countercurrent manner (i.e., adding in the direction opposite to the stirring direction of the mixed slurry), and a more dense aluminum oxide film can be formed. Furthermore, the present application controls the temperature of the mixed slurry to be 63-67° C., the deposition time to be 105-110 min, and the amount of sodium aluminate solution added to be 2.2-2.3% of the mass of TiO2 in terms of Al2O3.

[0014] In order to further improve the stability of the overall structure of the product and make titanium dioxide easier to carry out other subsequent processing and applications, such as grafting modification, the present application also deposits a relatively loose aluminum oxide film on the dense aluminum oxide film. Adjust the rotation speed to 50-58r / min, and quickly and evenly add sodium aluminate solution in a short period of time. The concentration of the sodium aluminate solution is 175-200g / L in terms of Al2O3. Further, a sodium aluminate solution with a concentration of 180-185g / L in terms of Al2O3 is selected. In this step, the present application adds aluminum sulfate solution in a downstream manner to adjust the pH value so as to complete the deposition of the loose aluminum oxide film. Furthermore, the present application adjusts the rotation speed to 52-58r / min, controls the temperature of the mixed slurry to 48-54°C, the deposition time to 45-55min, the amount of sodium aluminate solution added is 1.35-1.5% of the mass of TiO2 in terms of Al2O3, and the pH value is adjusted to 7.2-7.3 with aluminum sulfate solution.

[0015] Preferably, in step S1, the method for preparing titanium dioxide slurry comprises the following steps: The primary titanium dioxide is slurried with desalted water to obtain a slurry with a titanium dioxide mass concentration of 33-35%, and then the slurry pH is adjusted to 9.5, followed by adding a dispersant for stirring and dispersion, followed by screening to remove hard particles larger than 45 μm, and then grinding, and finally cyclone classification treatment to remove large particles larger than 5 μm to obtain titanium dioxide slurry.

[0016] By adopting the above technical scheme, the present application prepares primary titanium dioxide by pulping with desalted water and adding a dispersant for dispersion, and then sequentially undergoes combined screening by a vibrating screen, grinding by a sand mill, and diversion by a cyclone classifier to grind and open agglomerates to the maximum extent, remove large particles, and ensure that the primary titanium dioxide has a good optical performance index foundation.

[0017] Preferably, the CBU index of the primary titanium dioxide is 11-13.

[0018] Through the above technical solution, the present application controls the CBU index of the primary titanium dioxide (CBU is the carbon black base color, which represents the comprehensive index of the properties of titanium dioxide particles), so that the final titanium dioxide powder has the index basis of the neutral tone required for high hiding power. The primary titanium dioxide of the present application is prepared by the chloride production process, and because the optical performance index of the chloride rutile titanium dioxide is better, it is used as the basic raw material.

[0019] Optionally, the dispersant is one of sodium silicate, sodium hexametaphosphate, citric acid and sorbic acid.

[0020] The present application uses citric acid as a dispersant, and the amount of the added citric acid content in the slurry is 0.3-0.35% of the mass fraction of TiO2, and the mixture is stirred thoroughly for 30-35 minutes.

[0021] Preferably, the screening process is: passing through a 100 mesh sieve, a 200 mesh sieve and a 325 mesh sieve in sequence.

[0022] Through the above technical solution, the present application uses a 100 mesh / 200 mesh / 325 mesh combined vibrating screen to first separate larger hard particles larger than 45 μm, fully eliminating relatively large hard particles produced by sintering a small amount of titanium dioxide material due to high temperature in the oxidation reaction of the chlorination process. In addition, the present application uses a combination of screens of different specifications, which can adapt to the characteristics of titanium dioxide slurry and reduce the possibility of screen clogging in actual production.

[0023] Preferably, in step S5, a green organic treatment agent is added during pulverization for organic treatment, and the amount of the green organic treatment agent added is 0.25-0.6% of the carbon content in the dried product.

[0024] Optionally, the green organic treatment agent is an amphiphilic polyol and / or an organosilicon dispersing aid.

[0025] Optionally, the green organic treatment agent is one or more of trimethylolethane, ethylene glycol, dimethyl silicone oil, titanate coupling agent, and dimethylolpropionic acid.

[0026] Preferably, the green organic treatment agent is a mixture of trimethylolethane and dimethylolpropionic acid.

[0027] Through the above technical scheme, the present application adds an amphiphilic green organic treatment agent to perform green organic composite coating during high-temperature and high-pressure steam pulverization, which can enhance the compatibility and dispersibility of titanium dioxide in water-based paints and oil-based paints, so that titanium dioxide can fully play its pigment role and improve the weather resistance and anti-powdering properties of the coating product.

[0028] The amphiphilic green organic treatment agent of the present application is added at the outlet of the steam powder machine, and is added simultaneously with the ground material by continuous quantitative gas atomization, which can ensure that the green organic treatment agent is evenly and stably distributed on the surface of titanium dioxide.

[0029] The present application further selects trimethylolethane and dimethylolpropionic acid for mixed use, which can further improve the dispersibility of titanium dioxide and enhance the glossiness of titanium dioxide.

[0030] In a second aspect, the present application provides a multi-component composite coated titanium dioxide prepared by the above-mentioned preparation method.

[0031] In summary, this application has the following beneficial technical effects: 1. The present application adopts three coating materials, namely silicon, zirconium and aluminum, to design a film layer combination, and optimizes the various parameters required for the coating process according to the slurry state, pH control rate, temperature and stirring and dispersing conditions of different coating processes, so that the surface of the titanium dioxide prepared by the present application is coated with a dense silicon oxide film layer, a dense zirconium oxide film layer, and a dense and loose aluminum oxide film layer. Compared with the existing binary composite coating and general-purpose titanium dioxide products with medium and low coating amounts, the titanium dioxide of the present application has significantly improved optical performance indicators and weather resistance, and can meet the development needs of coatings in high weather resistance and emerging environmental protection fields such as ships, bridges, solar energy, and wind power; 2. The present application controls the CBU index of primary titanium dioxide, and after pulping the primary titanium dioxide that meets the CBU index requirements with desalted water and adding a dispersant to disperse it, it is sequentially subjected to a combination of screening by a vibrating screen, grinding by a sand mill, and diversion by a cyclone classifier to grind and open the agglomerates to the maximum extent, remove large particles, and improve the optical performance index basis of the primary titanium dioxide; 3. The present application adds an amphiphilic green organic treatment agent during high-temperature and high-pressure steam flow pulverization for green organic composite coating, which can enhance the compatibility and dispersibility of titanium dioxide in water-based paints and oil-based paints, so that titanium dioxide can fully exert its pigment function and improve the weather resistance and anti-powdering properties of the coating product. DETAILED DESCRIPTION

[0032] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0033] The raw materials used in this application, except for primary titanium dioxide, are all commercially available products.

[0034] The primary titanium dioxide of the present application is a semi-finished product of rutile titanium dioxide produced by the chloride process, and its preparation method is a conventional process method in the field. Since the purpose of the present application is to coat and modify the primary titanium dioxide, the preparation method of the primary titanium dioxide will not be described in detail in the present application.

[0035] Example 1.1 A method for preparing a multi-component composite coated titanium dioxide comprises the following steps: S11. Add desalted water to 500 kg of primary titanium dioxide with a CBU index of 12 and stir and disperse for 30 min to obtain a titanium dioxide slurry with a mass concentration of 33%, then adjust the slurry pH to 9.5 with a 20% sodium hydroxide solution, add 0.35% citric acid with a TiO2 mass fraction and stir and disperse for 30 min, then sequentially pass through 100 mesh / 200 mesh / 325 mesh combination vibrating screen screening, sand mill grinding and cyclone classifier shunting to obtain a primary titanium dioxide slurry; S12. The primary titanium dioxide slurry is added to the coating tank, the stirrer speed is adjusted to 60r / min, the pH value is adjusted to 9.0 with a 20% sodium hydroxide solution, and desalted water is added to make the mass concentration of the titanium dioxide slurry 25%. After fully dispersing for 30 minutes, the titanium dioxide slurry is heated to 65°C; S13. Add sodium silicate solution with a concentration of 150 g / L in terms of SiO2 and a mass of 3.5% of the mass of TiO2 to the titanium dioxide slurry, stir and disperse for 30 minutes to obtain a mixed slurry, then control the temperature of the mixed slurry to 76°C, adjust the speed to 50 r / min, first slowly and evenly adjust and control the pH value of the mixed slurry to 8.8 with a hydrochloric acid solution with a mass concentration of 9% within 180 minutes, complete the deposition of the first layer of dense silicon film, and then slowly and evenly adjust the pH value of the mixed slurry to 8.8 with a hydrochloric acid solution with a mass concentration of 9% within 90 minutes. S2. Continue to control the temperature of the mixed slurry to 58°C, adjust the rotation speed to 60r / min, and continuously and evenly add zirconium sulfate solution with a concentration of 165g / L in terms of ZrO2 and a mass of 0.6% of the mass of TiO2 in terms of ZrO2 within 200min, and at the same time control the pH value of the mixed slurry to 9.3 with a sodium hydroxide solution with a mass concentration of 20%, complete the coating of the dense zirconium film, and then stir and mature for 60min; S3. Continue to control the temperature of the mixed slurry to 65 ° C, adjust the speed to 55r / min, and continuously and evenly add a sodium aluminate solution with a concentration of 145g / L in terms of Al2O3 and a mass of 2.0% of the mass of TiO2 in terms of Al2O3 within 90min. When the pH value of the mixed slurry reaches 9.2, a 10% sulfuric acid solution is slowly added by countercurrent to control the pH value of the mixed slurry at 9.3 to complete the coating of the dense aluminum film, and then stir and mature for 50min; S4. Continue to control the temperature of the mixed slurry to 50 ° C, adjust the speed to 55r / min, and continuously and evenly add a sodium aluminate solution with a concentration of 175g / L in terms of Al2O3 and a mass of 1.3% of the mass of TiO2 in terms of Al2O3 within 50min, and at the same time add an aluminum sulfate solution with a concentration of 100g / L in terms of Al2O3 in a downstream manner, control the pH value of the mixed slurry to 7.5, complete the coating of the loose aluminum film, and then stir and mature for 50min; S5. The endpoint pH value of the mixed slurry is adjusted to 7.0, and stirring and aging is continued for 90 minutes. Then, the slurry is homogenized, filtered, washed, dehydrated, dried, and crushed. During the crushing, trimethylolethane and dimethylolpropionic acid with a volume ratio of 1:1 are added to the ground material at the outlet of the steam powder machine by continuous quantitative gas atomization for green organic composite coating. The total amount of trimethylolethane and dimethylolpropionic acid added is 0.6% of the carbon content in the dried product to obtain multi-component composite coated titanium dioxide.

[0036] Example 1.2 A method for preparing a multi-component composite coated titanium dioxide comprises the following steps: S11. Add desalted water to 500 kg of primary titanium dioxide with a CBU index of 11.5 and stir and disperse for 30 min to obtain a titanium dioxide slurry with a mass concentration of 35%, then adjust the slurry pH to 9.5 with a 20% sodium hydroxide solution, add 0.3% citric acid with a TiO2 mass fraction and stir and disperse for 35 min, and then sequentially pass through 100 mesh / 200 mesh / 325 mesh combination vibrating screen screening, sand mill grinding and cyclone classifier shunting to obtain a primary titanium dioxide slurry; S12. The primary titanium dioxide slurry is added to the coating tank, the stirrer speed is adjusted to 65r / min, the pH value is adjusted to 10.5 with a 20% sodium hydroxide solution, and desalted water is added to make the mass concentration of the titanium dioxide slurry 23%. After fully dispersing for 40 minutes, the titanium dioxide slurry is heated to 75°C; S13. Add a sodium silicate solution having a concentration of 180 g / L in terms of SiO2 and a mass of 3.8% of the mass of TiO2 in terms of SiO2 to the titanium dioxide slurry, stir and disperse for 40 minutes to obtain a mixed slurry, then control the temperature of the mixed slurry to 78°C, adjust the rotation speed to 55 r / min, slowly and evenly adjust and control the pH value of the mixed slurry to 9.0 with a hydrochloric acid solution having a mass concentration of 10% within 200 minutes, complete the deposition of the first layer of dense silicon film, then slowly and evenly adjust and control the pH value of the mixed slurry to 7.5 with a hydrochloric acid solution having a mass concentration of 10% within 100 minutes, complete the deposition of the second layer of dense silicon film, and then stir and mature for 110 minutes; S2. Continue to control the temperature of the mixed slurry to 62 ° C, adjust the speed to 65r / min, and continuously and evenly add a zirconium sulfate solution with a concentration of 175g / L in terms of ZrO2 and a mass of 0.7% of the mass of TiO2 in terms of ZrO2 within 220min, and control the pH value of the mixed slurry to 9.5 with a sodium hydroxide solution with a mass concentration of 20%, complete the coating of the dense zirconium film, and then stir and mature for 60min; S3. Continue to control the temperature of the mixed slurry at 60 ° C, adjust the speed to 65r / min, and continuously and evenly add a sodium aluminate solution with a concentration of 160g / L in terms of Al2O3 and a mass of 2.5% of the mass of TiO2 in terms of Al2O3 within 110min. When the pH value of the mixed slurry reaches 9.4, a 10% sulfuric acid solution is slowly added by countercurrent to control the pH value of the mixed slurry to 9.5, complete the coating of the dense aluminum film, and then stir and mature for 50min; S4. Continue to control the temperature of the mixed slurry to 55 ° C, adjust the speed to 50r / min, and continuously and evenly add a sodium aluminate solution with a concentration of 200g / L in terms of Al2O3 and a mass of 1.2% of the mass of TiO2 in terms of Al2O3 within 60min, and at the same time add an aluminum sulfate solution with a concentration of 100g / L in terms of Al2O3 in a downstream manner, control the pH value of the mixed slurry to 7.8, complete the coating of the loose aluminum film, and then stir and mature for 50min; S5. The endpoint pH value of the mixed slurry is adjusted to 7.2, and the stirring and aging is continued for 100 minutes. Then, the slurry is homogenized, filtered, washed, dehydrated, dried, and crushed. During the crushing, trimethylolethane and dimethylolpropionic acid with a volume ratio of 1:1 are added to the ground material at the outlet of the steam powder machine by continuous quantitative addition of gas atomization to carry out green organic composite coating. The total amount of trimethylolethane and dimethylolpropionic acid added is 0.25% of the carbon content in the dried product to obtain multi-component composite coated titanium dioxide.

[0037] Example 2.1 A method for preparing a multi-component composite coated titanium dioxide powder, which differs from Example 1.1 in that: in step S12, the agitator speed is adjusted to 70 r / min, the pH value is adjusted to 10.5 with a sodium hydroxide solution with a mass concentration of 20%, and desalted water is added to make the mass concentration of the titanium dioxide slurry 22%. After being fully dispersed for 40 minutes, the titanium dioxide slurry is heated to 68°C, and the rest is the same as Example 1.1.

[0038] Example 2.2 A method for preparing a multi-component composite coated titanium dioxide powder, which differs from Example 1.1 in that: in step S12, the agitator speed is adjusted to 65 r / min, the pH value is adjusted to 11.0 with a sodium hydroxide solution with a mass concentration of 20%, and desalted water is added to make the mass concentration of the titanium dioxide slurry 23%. After being fully dispersed for 35 minutes, the titanium dioxide slurry is heated to 72°C, and the rest is the same as Example 1.1.

[0039] Example 3.1 A method for preparing a multi-component composite coated titanium dioxide powder, which differs from Example 1.1 in that: in step S13, a sodium silicate solution with a concentration of 170 g / L in terms of SiO2 and a mass of 3.6% of the mass of TiO2 in terms of SiO2 is added to the titanium dioxide slurry, and the mixed slurry is obtained after stirring and dispersing for 40 minutes, and then the temperature of the mixed slurry is controlled to 74°C, the rotation speed is adjusted to 55 r / min, and the pH value of the mixed slurry is first slowly and evenly adjusted and controlled to 8.8 with a hydrochloric acid solution with a mass concentration of 11% within 190 minutes to complete the deposition of the first layer of dense silicon film, and the rest is the same as Example 1.1.

[0040] Example 4.1 A method for preparing a multi-component composite coated titanium dioxide, which differs from Example 1.1 in that: in step S2, the temperature of the mixed slurry is controlled to 60°C, the rotation speed is adjusted to 65r / min, and a zirconium sulfate solution with a concentration of 175g / L in terms of ZrO2 and a mass of 0.62% of the mass of TiO2 in terms of ZrO2 is continuously and evenly added within 210min; the rest is the same as Example 1.1.

[0041] Example 5.1 A method for preparing a multi-component composite coated titanium dioxide, which differs from Example 1.1 in that: in step S3, the temperature of the mixed slurry is controlled to 63°C, the rotation speed is adjusted to 65r / min, and a sodium aluminate solution with a concentration of 150g / L in terms of Al2O3 and a mass of 2.2% of the mass of TiO2 in terms of Al2O3 is continuously and evenly added within 110min; when the pH value of the mixed slurry reaches 9.3, a sulfuric acid solution with a mass concentration of 10% is slowly added in a countercurrent manner to control the pH value of the mixed slurry to 9.1; the rest is the same as Example 1.1.

[0042] Example 5.2 A method for preparing a multi-component composite coated titanium dioxide, which differs from Example 1.1 in that: in step S3, the temperature of the mixed slurry is controlled to 67°C, the rotation speed is adjusted to 60r / min, and a sodium aluminate solution with a concentration of 170g / L in terms of Al2O3 and a mass of 2.3% of the mass of TiO2 in terms of Al2O3 is continuously and evenly added within 105min; when the pH value of the mixed slurry reaches 8.9, a sulfuric acid solution with a mass concentration of 10% is slowly added in a countercurrent manner to control the pH value of the mixed slurry to 9.5; the rest is the same as Example 1.1.

[0043] Example 6.1 A method for preparing a multi-component composite coated titanium dioxide, which differs from Example 1.1 in that: in step S4, the temperature of the mixed slurry is controlled to 48°C, the rotation speed is adjusted to 58r / min, and a sodium aluminate solution with a concentration of 180g / L in terms of Al2O3 and a mass of 1.5% of the mass of TiO2 in terms of Al2O3 is continuously and evenly added within 55min, and at the same time, an aluminum sulfate solution with a concentration of 100g / L in terms of Al2O3 is added in a downstream manner, and the pH value of the mixed slurry is controlled to 7.3. The rest is the same as Example 1.1.

[0044] Example 6.2 A method for preparing a multi-component composite coated titanium dioxide, which differs from Example 1.1 in that: in step S4, the temperature of the mixed slurry is controlled to 54°C, the rotation speed is adjusted to 52r / min, and an aluminate solution with a concentration of 185g / L in terms of Al2O3 and a mass of 1.35% of the mass of TiO2 in terms of Al2O3 is continuously and evenly added within 45min, and at the same time, an aluminum sulfate solution with a concentration of 100g / L in terms of Al2O3 is added in a downstream manner, and the pH value of the mixed slurry is controlled to 7.2. The rest is the same as Example 1.1.

[0045] Comparative Example 1 The preparation method of zirconium-aluminum composite coated titanium dioxide comprises the following steps: a. Add desalted water to 500 kg of primary titanium dioxide and stir and disperse for 30 min to obtain a titanium dioxide slurry with a mass concentration of 28%, then adjust the slurry pH to 9.5 with a 20% mass concentration of sodium hydroxide solution, then add 0.3% sodium hexametaphosphate with a TiO2 mass fraction and stir and disperse for 30 min, and then grind with a sand mill to obtain a titanium dioxide slurry; b. Add the titanium dioxide slurry to the coating tank, adjust the stirrer speed to 60r / min, adjust the pH value to 9.0 with a 20% sodium hydroxide solution, and add desalted water to make the mass concentration of the titanium dioxide slurry 26%. After fully dispersing for 30 minutes, heat the titanium dioxide slurry to 60°C; c. Add zirconium sulfate solution with a concentration of 165 g / L in terms of ZrO2 and a mass of 0.45% of the mass of TiO2 in terms of ZrO2 continuously and uniformly within 120 min, and control the pH value of the mixed slurry to 8.6±0.4 with a 20% mass concentration of sodium hydroxide solution, and then stir and mature for 60 min; d. Continue to control the temperature of the mixed slurry at 55°C, adjust the speed to 55r / min, and continuously and evenly add a sodium aluminate solution with a concentration of 145g / L in terms of Al2O3 and a mass of 1.8% of the mass of TiO2 in terms of Al2O3 within 70min, and slowly add an aluminum sulfate solution with a mass concentration of 105g / L in terms of Al2O3 in a downstream manner, control the pH value of the mixed slurry to 7±0.2, and then stir and mature for 30min; e. The endpoint pH value of the mixed slurry is adjusted to 7.0, and stirring and aging is continued for 100 minutes, and then homogenized, filtered, washed, dehydrated, dried, and crushed. During the crushing, trimethylolpropane is continuously and quantitatively added to the material at the feed port of the steam powder machine by pumping. The amount of trimethylolpropane added is 0.35% of the carbon content in the dried product to obtain zirconium-aluminum composite coated titanium dioxide.

[0046] Comparative Example 2 The method for preparing silicon-aluminum composite coated titanium dioxide comprises the following steps: I. Add desalted water to 500 kg of primary titanium dioxide and stir and disperse for 30 minutes to obtain a titanium dioxide slurry with a mass concentration of 30%, then adjust the slurry pH to 9.8 with a sodium hydroxide solution with a mass concentration of 20%, then add sodium silicate with a TiO2 mass fraction of 0.4% and stir and disperse for 30 minutes, then grind with a sand mill to obtain a titanium dioxide slurry; II. Add the titanium dioxide slurry to the coating tank, adjust the stirrer speed to 60r / min, adjust the pH value to 10.5 with a 20% sodium hydroxide solution, and add desalted water to make the mass concentration of the titanium dioxide slurry 25%. After fully dispersed for 30 minutes, add a sodium silicate solution with a concentration of 180g / L in terms of SiO2 and a mass of 2.5% of the mass of TiO2 in terms of SiO2 to the titanium dioxide slurry at one time, stir and disperse for 50 minutes to obtain a mixed slurry, then control the temperature of the mixed slurry to 65°C, adjust the speed to 40r / min, slowly and evenly adjust and control the pH value of the mixed slurry to 8.8±0.2 with a 15% sulfuric acid solution within 150 minutes, and stir and mature for 40 minutes; III. Continue to control the temperature of the mixed slurry at 55 ° C, adjust the speed to 55r / min, and continuously and evenly add a sodium aluminate solution with a concentration of 165g / L in terms of Al2O3 and a mass of 1.5% of the mass of TiO2 in terms of Al2O3 within 50min, and slowly add an aluminum sulfate solution with a mass concentration of 100g / L in terms of Al2O3 in a downstream manner, adjust the pH value of the mixed slurry to 7±0.1, and then stir and mature for 40min; IV. The endpoint pH value of the mixed slurry is adjusted to 7.0, and stirring and aging is continued for 120 minutes, and then it is homogenized, filtered, washed, dehydrated, dried, and crushed. During the crushing, trimethylolpropane is continuously and quantitatively added to the material at the feed port of the steam powder machine by means of a pump. The amount of trimethylolpropane added is 0.3% of the carbon content in the dried product to obtain silicon-aluminum composite coated titanium dioxide.

[0047] Comparative Example 3 The method for preparing silicon-aluminum composite coated titanium dioxide comprises the following steps: I. Add desalted water to 500 kg of primary titanium dioxide and stir and disperse for 30 minutes to obtain a titanium dioxide slurry with a mass concentration of 31%, then adjust the slurry pH to 9.8 with a sodium hydroxide solution with a mass concentration of 20%, then add sodium silicate with a TiO2 mass fraction of 0.4% and stir and disperse for 30 minutes, then grind with a sand mill to obtain a titanium dioxide slurry; II. Add the titanium dioxide slurry to the coating tank, adjust the stirrer speed to 60r / min, adjust the pH value to 10.5 with a 20% sodium hydroxide solution, and add desalted water to make the mass concentration of the titanium dioxide slurry 25%. After fully dispersed for 30 minutes, add a sodium silicate solution with a concentration of 180g / L in terms of SiO2 and a mass of 2.6% of the mass of TiO2 in terms of SiO2 to the titanium dioxide slurry at one time, stir and disperse for 50 minutes to obtain a mixed slurry, then control the temperature of the mixed slurry to 65°C, adjust the speed to 50r / min, slowly and evenly adjust and control the pH value of the mixed slurry to 8.8±0.2 with a 15% sulfuric acid solution within 150 minutes, and stir and mature for 40 minutes; III. Continue to control the temperature of the mixed slurry at 55 ° C, adjust the speed to 50r / min, and continuously and evenly add a sodium aluminate solution with a concentration of 175g / L in terms of Al2O3 and a mass of 3.2% of the mass of TiO2 in terms of Al2O3 within 55 minutes, and slowly add a sulfuric acid solution with a mass concentration of 15% in a downstream manner, adjust the pH value of the mixed slurry to 7±0.1, and then stir and mature for 50 minutes; IV. The endpoint pH value of the mixed slurry is adjusted to 7.0, and stirring and aging is continued for 120 minutes, and then it is homogenized, filtered, washed, dehydrated, dried, and crushed. During the crushing, trimethylolpropane is continuously and quantitatively added to the material at the feed port of the steam powder machine by means of a pump. The amount of trimethylolpropane added is 0.4% of the carbon content in the dried product to obtain silicon-aluminum composite coated titanium dioxide.

[0048] Performance Testing 1. The titanium dioxide obtained in the above embodiments and comparative examples is directly subjected to a weather resistance test by an acid dissolution method. The principle is to use a chemical method to directly dissolve the titanium dioxide with concentrated sulfuric acid, and then calculate the coverage and density of the product according to the amount of dissolved titanium dioxide. A smaller value indicates a higher weather resistance. 2. Add 22% of the total weight of all components in the formula of the titanium dioxide prepared in the above embodiments and comparative examples to the water-based two-component polyurethane formula system, stir and disperse to make pulp at a speed of 1500 r / min. Except for the different sources of titanium dioxide, the other conditions of each experimental group are the same. Then, apply the film on the black and white plates, and detect the optical indicators with a spectrophotometer after drying. 3. Add 22% of the total weight of all components in the formula of the titanium dioxide obtained in the above embodiments and comparative examples to the water-based two-component polyurethane formula system, stir and disperse to make a slurry at a speed of 1500 r / min. The experimental groups are the same except for the different sources of titanium dioxide. Then, spray the film on the tinplate and dry it. Then, irradiate it with ultraviolet light for 1200 hours, and then detect the gloss change value of the sample at 60° before and after irradiation, and calculate the gloss loss rate. The smaller the gloss loss rate, the higher the weather resistance performance. The specific water-based two-component polyurethane formula system is: deionized water 10%, dispersant 490 1.85%, curing agent BYK-024 0.15%, titanium dioxide 22%, hydroxylated acrylic emulsion AH233 60%, other additives 6%; The above performance test results are shown in Table 1.

[0049] Table 1 Performance test results Data Analysis: As can be seen from Table 1, the main application performance indicators of the titanium dioxide prepared in Examples 1.1-6.2 of the present application in the water-based two-component polyurethane formulation system - brightness, hue, whiteness, dispersibility, and covering power and other pigment optical performance indicators are better than those of Comparative Examples 1-3, and the difference between all Examples 1.1-6.2 is small and relatively stable. The light loss rate and acid solubility value are lower than those of Comparative Examples 1-3, which shows that the titanium dioxide prepared in the present application has significantly improved weather resistance and anti-powdering performance, and the process is mature and stable, which can meet the development needs of coatings in high weather resistance and emerging environmental protection fields such as ships, bridges, solar energy, and wind power.

[0050] Among them, the difference between Examples 3.1-6.2 and Example 1.1 is that the process parameters of each step in the coating process are further changed. It can be seen from Table 1 that the weather resistance and anti-powdering properties of the titanium dioxide prepared in Examples 3.1-6.2 are slightly higher than those in Example 1.1, and the indicators are stable. This shows that Examples 3.1-6.2 can still ensure the weather resistance and anti-powdering performance indicators of titanium dioxide when the process parameters of each step in the coating process are further changed.

[0051] The existing process of comparative examples 1-3 is different from that of embodiment 1.1 in that: first, the particle size range of the primary titanium dioxide product is not selected, which affects the product hiding power index; second, conventional coating zirconium film and aluminum film are used, which affects the weather resistance index; third, conventional coating silicon film and aluminum film are used, which affects the gloss loss rate and weather resistance index; fourth, conventional trimethylolpropane is used for organic treatment, which affects the dispersibility index. As can be seen from Table 1, the hiding power, dispersibility, gloss loss rate and acid solubility of comparative examples 1-3 are significantly lower than those of embodiment 1.1, indicating that the innovative process composite multi-element coating formula obtained in this application can form dense silicon film, zirconium film, and dense and loose aluminum film on the surface of titanium dioxide, achieving the goal of significantly improving the weather resistance and anti-powdering performance of titanium dioxide.

[0052] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a multi-component composite coated titanium dioxide, characterized in that: The following steps are involved: S1. The titanium dioxide slurry and the silicate solution are stirred and dispersed to obtain a mixed slurry, wherein the temperature of the titanium dioxide slurry is 65-75°C, the mass concentration is 22-25%, the pH value is 9.0-11.0, and the amount of the silicate solution added is 3.5-3.8% of the mass of TiO2 in terms of SiO2, and then the temperature of the mixed slurry is controlled to 74-78°C, and the pH value of the mixed slurry is adjusted and controlled to 8.8-9.0 with an inorganic acid solution within 180-200 minutes while stirring, and the first layer of dense silicon film deposition is completed, and then the inorganic acid solution is used to adjust and control the pH value of the mixed slurry to 7.5-7.8 within 90-100 minutes, and the second layer of dense silicon film deposition is completed, and then stirred and matured for 100-110 minutes; S2. The temperature of the mixed slurry is controlled to be 58-62°C, and the zirconate solution is continuously added within 200-220min while stirring, and the pH value of the mixed slurry is controlled to be 9.3-9.5 with an alkaline solution to complete the deposition of a dense zirconium film, wherein the amount of the zirconate solution added is 0.6-0.7% of the mass of TiO2 in terms of ZrO2, and then stirred and aged for 60min; S3. Continue to adjust and control the temperature of the mixed slurry to 60-67 ° C, and continuously add aluminate solution within 90-110 min while stirring, wherein the amount of the aluminate solution added is 2.0-2.5% of the mass of TiO2 in terms of Al2O3, and the pH value of the mixed slurry is controlled to 8.9-9.5 with an inorganic acid solution, and the inorganic acid solution is added in a countercurrent manner, and then stirred and matured for 50 min; S4. Continue to adjust and control the temperature of the mixed slurry to 48-55 ° C, and continuously add aluminate solution within 45-60 minutes while stirring, wherein the amount of the aluminate solution added is 1.2-1.5% of the mass of TiO2 in terms of Al2O3, and the pH value of the mixed slurry is controlled to 7.2-7.8 with aluminum sulfate solution, and the aluminum sulfate solution is added in a downstream manner, and then stirred and matured for 50 minutes; S5. The end point pH value of the mixed slurry is adjusted to 7.0-7.2, and the stirring and aging are continued for 90-100 minutes, and then the mixed slurry is homogenized, filtered, washed, dehydrated, dried, crushed and organically treated to obtain a multi-component composite coated titanium dioxide.

2. The method for preparing a multi-component composite coated titanium dioxide according to claim 1, characterized in that: In step S1, the method for preparing titanium dioxide slurry comprises the following steps: The primary titanium dioxide is slurried with desalted water to obtain a slurry with a titanium dioxide mass concentration of 33-35%, and then the slurry pH is adjusted to 9.5, followed by adding a dispersant for stirring and dispersion, followed by screening to remove hard particles larger than 45 μm, and then grinding, and finally cyclone classification treatment to remove large particles larger than 5 μm to obtain titanium dioxide slurry.

3. The method for preparing a multi-component composite coated titanium dioxide according to claim 2, characterized in that: The CBU index of the primary titanium dioxide is 11-13.

4. The method for preparing a multi-component composite coated titanium dioxide according to claim 2, characterized in that: The dispersant is one of sodium silicate, sodium hexametaphosphate, citric acid and sorbic acid.

5. The method for preparing a multi-component composite coated titanium dioxide according to claim 2, characterized in that: The screening process is: passing through a 100-mesh sieve, a 200-mesh sieve and a 325-mesh sieve in sequence.

6. The method for preparing a multi-component composite coated titanium dioxide according to claim 1, characterized in that: In the step S5, a green organic treatment agent is added during the pulverization for organic treatment, and the amount of the green organic treatment agent added is 0.25-0.6% of the carbon content in the dried product.

7. The method for preparing a multi-component composite coated titanium dioxide according to claim 6, characterized in that: The green organic treatment agent is an amphiphilic polyol and / or an organosilicon dispersing aid.

8. The method for preparing a multi-component composite coated titanium dioxide according to claim 7, characterized in that: The green organic treatment agent is one or more of trimethylolethane, ethylene glycol, dimethyl silicone oil, titanate coupling agent, and dimethylol propionic acid.

9. The method for preparing a multi-component composite coated titanium dioxide according to claim 8, characterized in that: The green organic treatment agent is a mixture of trimethylolethane and dimethylolpropionic acid.

10. A multi-component composite coated titanium dioxide prepared by the method for preparing the multi-component composite coated titanium dioxide according to any one of claims 1 to 9.

Citation Information

Cited By

  • Preparation method of high-fluidity and low-dust titanium dioxide for multiple fields

    CN121699431A

  • Film coating method and application of titanium dioxide coated with high-silicon-content compact silicon-aluminum

    CN121825283A

  • Titanium dioxide with multi-component composite coating, and preparation method therefor

    WO2026081678A1